2022
DOI: 10.3389/fsufs.2022.835978
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Analysis of Banana (Musa acuminata) Treated With Chitosan Coating and Low Temperature Reveals Different Mechanisms Modulating Delayed Ripening

Abstract: Banana (Musa acuminata) is one of the most important crop plants consumed in many countries. However, the commercial value decreases during storage and transportation. To maintain fruit quality, postharvest technologies have been developed. Storage at low temperature is a common method to prolong the shelf life of food products, especially during transportation and distribution. Another emerging approach is the use of chitosan biopolymer as an edible coating, which can extend the shelf life of fruit by prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The regulation of signalling cascades like how plants discriminate the signalling components and their specific combinations for activating specific downstream biological processes for a given stress can be explained by metabolomics approach. However, metabolomics studies were carried out in banana only to elucidate the pseudostem elongation (Deng et al, 2021), post‐harvest senescence (Yuan et al, 2017) and ripening (Parijadi et al, 2022). Several morphological and physiological traits associated with cold tolerance if addressed to a greater extent would markedly strengthen the success in molecular biology.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The regulation of signalling cascades like how plants discriminate the signalling components and their specific combinations for activating specific downstream biological processes for a given stress can be explained by metabolomics approach. However, metabolomics studies were carried out in banana only to elucidate the pseudostem elongation (Deng et al, 2021), post‐harvest senescence (Yuan et al, 2017) and ripening (Parijadi et al, 2022). Several morphological and physiological traits associated with cold tolerance if addressed to a greater extent would markedly strengthen the success in molecular biology.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Chitosan is a natural cationic polysaccharide created by deacetylating the chitin that is found in animal shells, such as crustaceans, insect cuticles, and yeast [64]. In recent years, chitosan has been applied in several foods, like sweet cherries [104], kiwifruit [105] mango [106], litchi [107], grape [65,108,109] apricot [110], banana [111], and papaya [112], among others. Prathibhani et al [105] studied the effect of an edible coating of chitosan in kiwifruit and showed that this coating has an effective preservation technique, reducing respiration activity and delaying the changes in weight loss and firmness, thereby delaying ripening.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…For the metabolomics study, the metabolite profiles of chitosan and low temperature-treated banana was used to study the delay of the ripening mechanism on M. acuminata cv. Cavendish fruit [49]. A study on comparative genomics was also conducted to reveal variations among some ripening-related genes between M. acuminata and M. balbisiana, namely pectin methylesterase (PME) and pectin methylesterase inhibitor (PMEI) which are responsible for cell wall remodelling [50].…”
Section: Future Researchmentioning
confidence: 99%